Monitoring flame soot maturity by variable temperature Raman spectroscopy. (1st August 2022) - Commodo, Mario; Serra, Gianluca; Bocchicchio, Serafina; Minutolo, Patrizia; Tommasini, Matteo; D'Anna, Andrea
Highlights: Temperature-dependent Raman spectra measurements for structural characterization of just-nucleated and aged/mature soot. Determination of the thermal coefficients ( χG ) of the Raman G band position. χG is a proxy of in-plane thermal expansion coefficient within the layers of polycondensed rings and depends on disorder. χG correlates to soot density and can be employed for the analysis of soot maturity. Abstract: Flame-formed soot nanoparticles are known to possess different nanostructures as a function of a large variety of combustion operative parameters, including particle residence time in flames, flame stoichiometry, fuel chemical composition, temperature and pressure. This implies that important properties ( e.g., soot oxidation reactivity, optical and electronic gap) may be different depending on the way soot particles are generated. Hence, it is beneficial to develop diagnostic methods that are sensitive to such differences among the various kinds of soot particles. In this work we investigate by off-line variable-temperature Raman spectroscopy two types of soot particles, namely just-nucleated and aged/mature particles, with a different size and maturity degree. The results obtained for soot particles have been compared and discussed with those found for other related carbon materials. As the Raman spectra are recorded at increasing sample temperature, from 300 to 525 K, both soots display a linear downshift of the position of the two main Raman modes (D and G bands). Just-nucleated soot particles exhibit the strongest temperature dependence of the position of the G band. Based on results from density functional theory calculations, interpreted by a simple empirical model, the observed temperature coefficient differences can be ascribed to differences in the nanostructural order of the two soot samples, which causes a different thermal expansion behavior.